The effect of local corruption on ownership strategy in cross border mergers and acquisitions - Emanuela Marrocu; Maria Chiara Di Guardo; Raffaele Paci (European Regional Science Association (ERSA), 2015)
This paper focuses on how corruption affects an important internationalization behavior of firms: the extent of control - wholly owned subsidiary or equity participation - exercised by firms involved in cross-border mergers and acquisitions (M&A). Recently, scholars have recommended studying the effect on ownership entry mode of the quality of the target country?s overall governance infrastructure, or of its most important dimensions (Slangen and Van Tulder 2009). Among these dimensions, one of the most relevant, due to its broad effect on the economy, is corruption. Corruption can be thought of as anything that counters the legal system or that can be viewed as an inappropriate business practice (Lambert-Mogiliansky et al. 2007), which raises the level of external uncertainty in the target country and thus the cost of doing business abroad in general and specifically in the realm of M&A (see Weitzel and Berns, 2006). Although the level of corruption of the host countries is expected to have a strong influence on management decisions during acquisitions, it has been overlooked in the academic literature, and research on this topic is in its infancy. As a matter of fact, the increasing trend toward international acquisitions has created the need to address whether the extant conceptual framework and empirical evidence on international acquisitions and corruption are adequate in explaining the firm?s decision control-wise. We analyze individual data on cross-border M&A carried out by firms located in the seven largest European countries, namely Germany, France, Italy, the Netherlands, Spain, Sweden and the United Kingdom, and operating in the 10 SIC divisions. We thus consider 20,034 international M&A deals completed in 137 host countries over the period 2000-2012. We find that the relationship between the level of corruption in the host country and the firm?s probability of opting for full control mode in cross-border M&A is U-shaped. Such a relationship suggests that ownership strategy will change depending on whether the corruption is low, moderate or high. Moreover, we contribute to the extant literature by demonstrating that technological relatedness between acquirer and target and the level of connectivity (in terms of trade intensity, historical linkage, and geographic proximity) between home and host countries moderates the relationship between corruption in the host country and the level of control. Finally, after controlling for a wide range of both firm (status, industrial sector, past experience, and ownership structure) and country (culture, legal strength, risk, democracy, and business easiness) features, we found that trade intensity exerts the strongest moderating effect on corruption.
Keywords: C31; D73; F23; G34; 330; mergers-acquisitions; corruption; ownership strategy; technological relatedness